Faktor Yang Berhubungan Dengan Kepatuhan Ibu Hamil Dalam Mengonsumsi Tablet FE Di UPTD Puskesmas Kuta Baharu Kecamatan Kota Baharu Kabupaten Aceh Singkil Tahun 2023 - Yasrida Nadeak; Rahmani Rahmani; Rasmi Manullang; Lasria Yolivia Aruan; Polma Ria Metawati Panjaitan; Humaida Hanim (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pregnant women are the result of fertilization from sperm which causes the mother to carry a fetus in her womb, namely in her uterus. According to a 2014 WHO and UN International Children's Emergency Fund (UNICEF) estimate in an Azinar discussion, that 529,000 women still die every year from complications of their pregnancy, and nearly 90% of these deaths occur in sub-Saharan Africa. and Asia. According to the Indonesian Ministry of Health, the number of mothers who died was caused by pregnancy and childbirth, reaching 5,019 people. Based on the initial survey conducted on March 13 to 15 2023 at at UPTD Puskesmas Kuta Baharu,Kota Baharu District Aceh Singkil Regency, there were 7 pregnant women. This research uses a quantitative analytic research type with a research design used in the form of a cross-sectional approach, where this cross-sectional design is a collection of research data that is carried out one time or at the same time. The purpose of this study was to determine the relationship between knowledge, the role of health workers and ANC on adherence to consuming Fe tablets in pregnant women. The population of this study were pregnant women in Aek Kanopan Hospital, North Labuhanbatu District. In this study the number of samples based on the formula with the total population and samples totaled 37 samples. The results showed that there was a relationship between knowledge and adherence to consuming Fe tablets in pregnant women with a p-value of 0.001 <0.05, the role of health workers with a p-value of 0.009 <0.05, family support with a p-value of 0.006 <0. 05 and ANC with a p-value of 0.002 <0.05 associated with adherence to consuming Fe tablets in pregnant women. There is a relationship between knowledge and adherence to consuming Fe tablets in pregnant women with a p-value of 0.001 <0.05. There is a relationship between the role of health workers and adherence to consuming Fe tablets in pregnant women with a p-value of 0.009 <0.05. There is a relationship between family support and adherence to consuming Fe tablets in pregnant women with a p-value of 0.006 <0.05. There is a relationship between ANC and adherence to consuming Fe tablets in pregnant women with a p-value of 0.002 <0.05.